The occurrence of bean common mosaic virus inwild and forage legume species in Uganda - Sengooba, T.N.K.; Walkey, D.G.A.; Spence, NJ; Allen, David J.; Lana, AF (International Center for Tropical Agriculture, 1994)
Necrosis inducing BCMV isolates were obtained from a range of wild and forage legume species growing in Uganda. Thirteen distinct isolates were identified on the bases of symptoms, pathogenicity in bean differential cultivars, serology, immunosorbent electron microscopy, seed-and aphid-transmission. Some isolates conformed with the characteristics of previously described strains but others showed novel properties. Two isolates (429 and 472) caused necrsois inI-gene carrying bean cultivars but gave negative tests against 1-2 monoclonal antibodies specific for "A" serotypes of BCMV. All isolates reinfected the natural host from which they were obtained. The origin and ecological significance of these isolates is discussed. (RA)